PSYCHOMETRIC VALIDATION AND URDU TRANSLATION OF CLINICAL ANGER SCALE - Dr. Anila Sadaf Mubashir; Dr. Faran Ali; Ms. Rida Kainaat; Quratulain; Ambar Muzzammil (Policy Research Journal, 2025)
The study aimed to translate the Clinical Anger Scale (CAS) into Urdu, assess language equivalence through cross-language validity, and confirm the factor structure of the Urdu version of CAS. The study was divided into three phases. The first phase focused on translating the CAS into Urdu. In the second phase, cross-language validation was conducted. The third phase involved establishing the reliability and factor structure of the CAS. A self-report questionnaire was developed to measure psychological symptoms related to clinical anger, consisting of 21 sets of statements with four options each. 700 participants aged 13 to 19 were selected, with 100 participants from each age group.Each age group included 50 boys and 50 girls, resulting in an overall sample of 350 boys and 350 girls. The results indicated test-retest reliability across all groups (English- Urdu, Urdu-English, Urdu-Urdu, and English-English), with correlation coefficients ranging from .75 to .82. The Urdu-Urdu group showed a correlation of r = .75 (p < .01), suggesting high temporal consistency. These correlations suggest excellent levels of test- retest reliability, confirming temporal validity and consistency of scores across the sample. Fit indices for the clinical anger scale were assessed, and the initial model showed excellent absolute fit (χ²(168) = 425.12, p < .05). Relative fit indices improved after modifications, resulting in GFI, CFI, and NNFI values of .97, .94, and .93 respectively, and RMSEA and SRMR values of .06 and .05 respectively, indicating excellent model fit. Reliability coefficients, including composite reliability and Cronbach’s alpha, ranged from .88 to .87, confirming the psychometrically sound and reliable nature of the scale. The study provides robust evidence supporting the language equivalence and theoretical similarity of the original and translated versions of the CAS.